EFEKTIVITAS PENERAPAN METODE GAMIFICATION BERBASIS ONLINE TERHADAP PENCAPAIAN KOMPETENSI PADA MAHASISWA UNIVERSITAS NEGERI MAKASSAR - Wahyu Hidayat M; Ali Mirza Najafi; Fariz Ramlan; Febrianti Tandi Ra’pak; Muhammad Alif Leo; Fadhlirrahman Baso (Jurnal Pendidikan Terapan, 2023)
Gamification is the application of game elements into applications to increase student motivation, interest and involvement in accessing and using applications. The development of the internet in the learning aspect has great potential to create a change in a more modern learning system that is in line with the digitalization that is currently occurring along with current technological developments.  The internet has characteristics as a learning medium, namely as an interactive learning medium, thus enabling synchronous and asynchronous communication between educators and students.  This study applies a quantitative research method with a survey approach.  Data analysis in this study used descriptive analysis method because the data obtained was in the form of numbers so it was necessary to use an approach to be able to process the statistical or mathematical data obtained.  The advantage of this method is that the conclusions obtained are more measurable and comprehensive.  The application of the gamification method in the online learning process has quite a big impact on competency achievement and the development of knowledge and skills in Makassar State University students